On the Relationship between the Amplification of the NMR Spin Echo Signal and the Mobility of Domain Walls in Cobalt Micro- and Nanowires During Magnetization Reversal - Mamniashvili, G; Gegechkori, T; Donadze, G; Ivanov, G (European Journal of Applied Sciences, 2026)
A comparative study of the amplification of the NMR two-pulse echo signal in polymer composites based on synthesized and commercial cobalt nano- and microwires during their magnetization reversal was carried out. For this purpose, the two-pulse NMR spin echo method was employed, incorporating an additional magnetic video pulse (MVP) in an external magnetic field. The echo signal enhancement effect in the case of synthesized microwires is much greater than that of commercial nanowires, which may be due to the lower pinning force of domain walls and their greater mobility in them. This information may be useful for improving the technology for manufacturing cobalt nano- and microwires for use in sensors, memory devices, and permanent magnets that do not contain rare-earth elements, as well as in other applications.